'Phoenix polymers': fire induced nanohardness in fibril-forming aromatic cyanate esters. Issue 63 (25th October 2018) - Mooring, Lyndsey; Thompson, Scott; Hall, Stephen A.; Pani, Silvia; Zioupos, Peter; Swan, Martin; Stone, Corinne; Howlin, Brendan J.; Hamerton, Ian
Abstract : For the first time we present nanoindentation analysis of charred, cured aromatic cyanate esters, which exhibit outstanding mechanical properties when analysed under applied loads of 0.1–300 mN. Abstract : For the first time we present nanoindentation analysis of charred, cured aromatic cyanate esters, which exhibit outstanding mechanical properties when analysed under applied loads of 0.1–300 mN. Following charring (900 °C for 10 minutes to achieve graphitised structures), the samples display a remarkable combination of a modulus of elasticity of around 25 GPa and nanohardness of 300 kgf mm −2, making them some 30–40% stiffer than bone and practically as hard as tooth enamel. At the same time we find that under the same conditions the chars are highly resilient, displaying complete elastic recovery with very little plastic deformation. When cured in the presence of copper(ii ) acetylacetonate (200 ppm) in dodecylphenol (1% w/v active copper suspension) to form a polycyanurate, compound (2 ) forms a dense, consolidated structure compared with compound (1 ) under the same conditions. At high magnification, the presence of a nanoscale, fibrillar structure is observed, accounting for the high resilience.